Digitalisasi untuk Penguatan Tata Kelola Koperasi Desa Merah Putih - Afril Efan Pajri; Ita Aristia Sa’ida (Jurnal Teras Pengabdian Masyarakat, 2026)
Digital transformation in cooperatives has become an urgent necessity in the era of Industry 4.0 and Society 5.0. This study aims to develop and implement a web-based cooperative management system in Koperasi Desa Merah Putih to enhance efficiency, accuracy, transparency, and member participation. The research employed a research and development (R&D) method with a participatory approach, involving cooperative managers and members throughout the stages of needs analysis, system design, implementation, and evaluation. The results indicate that the digital system significantly improves administrative efficiency by more than 50%, reduces recording errors by over 70%, and provides real-time financial reports accessible to members. Furthermore, the system fosters digital literacy among cooperative managers and members, although several challenges remain, such as limited internet infrastructure, human resource readiness, and the need for continuous system maintenance. Practically, this study offers a ready-to-use digital cooperative system that can serve as a model for other rural cooperatives. Academically, it strengthens the literature on cooperative digitalization as a strategy to enhance governance, build member trust, and promote sustainable rural economic development.